2007
DOI: 10.1002/cb.223
|View full text |Cite
|
Sign up to set email alerts
|

Computer ethics and consumer ethics: the impact of the internet on consumers' ethical decision‐making process

Abstract: Despite the maturity of the literatures that consider ethical consumer behaviour and the role of the internet, very little work seems to have been undertaken to bring these two themes together. This is unfortunate because the internet is increasingly pervasive and is used at some stage in a significant number of consumer activities. Our primary purpose is to bring together key insights and themes from research into both ethical consumer behaviour and the internet to highlight further research opportunities. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 69 publications
1
34
0
1
Order By: Relevance
“…A particular behaviour is considered the most ethical if there is a greater balance of good over bad compared to the other alternatives. Hunt and Vitell (1992;1986) revealed that an ethical decision process begins with a consumer perceiving an ethical problem and continues with the consumer combining a deontological and a teleological evaluation to arrive at a judgment or an attitude about the ethical problem (Chatzidakis and Mitussis, 2007). The ethical judgment may differ from the original intentions after examination of the probable consequences, and an individual's past behaviour and feedback on the actual consequences may affect their future behaviour.…”
Section: Hunt and Vitell's General Theory Of Marketing Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular behaviour is considered the most ethical if there is a greater balance of good over bad compared to the other alternatives. Hunt and Vitell (1992;1986) revealed that an ethical decision process begins with a consumer perceiving an ethical problem and continues with the consumer combining a deontological and a teleological evaluation to arrive at a judgment or an attitude about the ethical problem (Chatzidakis and Mitussis, 2007). The ethical judgment may differ from the original intentions after examination of the probable consequences, and an individual's past behaviour and feedback on the actual consequences may affect their future behaviour.…”
Section: Hunt and Vitell's General Theory Of Marketing Ethicsmentioning
confidence: 99%
“…If research on ethics focused only on suppliers, it will result in a deficient and biased understanding of the subject matter . Millions of dollars have been lost in counterfeiting and piracy; the impact of globalisation and the invention of the internet accelerated and highlighted consumer ethical issues, which in turn aroused researchers' attention such that they have shown increasing interest in the topic during the last two decades (Chatzidakis and Mitussis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Simpson (2006: 14) defines ‗e-crimes' as covering many different areas, including phishing, hacking, extortion, denial of service attacks, advanced fee fraud, money laundering; virus writing, distributing malicious code, bot-herding, grooming, distributing paedophile material, internet abuse in the work place, intellectual property theft, online piracy of copyright material, and spamming. Chatzidakis and Mitussis (2007) highlight the importance of the internet's scope on unethical internet behavior. The Internet permits the accomplishment of deviant consumer behavior anonymously and it also makes it more difficult to identify unethical activities.…”
Section: IImentioning
confidence: 96%
“…The explosive growth in the popularity of handheld Internet devices, 4 combined with significant government investments in broadband expansion, has dramatically increased Internet accessibility across the United States in recent years. 5 The Internet has become the most effective communication medium for consumers to explore issues such as genetically modified food production and fairtrade or organic certifications-it is unique in that it serves as both a communication medium and a site of consumer activity (Chatzidaks and Mitussis 2007). In theory, the Internet enables consumers to overcome many of the information asymmetries that characterize global food supply chains; it also more readily enables them to act collectively to impose sanctions on firms through their collective voice and veto power, thereby potentially playing a more active role in influencing food production practices.…”
Section: Traceability From Crop To Cupmentioning
confidence: 99%